Anti-PGK1 antibodies in immuno-related pancytopenia - Shanfeng Hao; Yang Zhang; Na Xiao; Rong Fu; Zonghong Shao (Hematology)
Objective Phosphoglycerate kinase 1 (PGK1) was previously screened as a possible autoantigen for IRP, this study further investigates the value of PGK1 autoantibodies in the diagnosis of IRP and their correlation with other clinical indicators.Method Anti-PGK1 antibodies were screened in untreated IRP patients and SAA patients by ELISA.CD5 + B cells and BMMNC-Ab were detected in untreated and recovered IRP patients by FCM. Clinical findings were compared between different groups.Result The serum level of anti-PGK1 antibodies of untreated IRP patients was significantly higher than that of SAA patients; the percentage of PGK1-Ab positive patients was lower in PLT > 50*109/L group in recovered IRP patients and PGK1-Ab levels in the recovered IRP patients were positively correlated with WBC and CIC levels and negatively correlated with PLT levels. PLT was positively correlated with CIC levels in the untreated IRP group. After treatment, the levels of C3 and C4, the percentage of CD34+ IgM positivity, and CD5+ B cells of IRP patients decreased significantly.Conclusion Detecting anti-PGK1 antibodies might have some clinical value in differentiating IRP from SAA. The tests of CD34+ IgM positivity, CD5+ B cells, and C3 and C4 levels are of clinical value in assessing the curative effect of IRP patients.